Analisis Kontrastif “Chuui Jikou” dalam Bahasa Jepang dan Bahasa Indonesia di Lembaga Pelatihan Kerja - Galih Mahesa Wibawa; Linna Meilia Rasiban; Herniawati Herniawati (Mezurashii: Journal of Japanese Studies, 2026)
This study aims to contrastively analyze the forms of chuui jikou (注意事項) or cautionary instructions in Japanese and Indonesian as used in Vocational Training Centers (LPK). The focus lies on syntactic structures of imperative sentences, including direct, indirect, and polite mitigated forms. Using a qualitative approach and descriptive method, the data were collected from 60 cautionary signs or instructional texts in training environments. The findings reveal that although both languages share similar syntactic structures, their usage patterns differ significantly. Japanese tends to employ polite and mitigated expressions such as ～てください and ～お願いします, whereas Indonesian frequently uses direct imperatives without mitigation. These results reflect differing pragmatic norms and communicative cultures between the two languages. This research contributes to cross-cultural understanding and Japanese language education in Indonesia.